2007
DOI: 10.1002/humu.20462
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants inMGMTand risk of lung cancer in Southeastern Chinese: a haplotype-based analysis

Abstract: O6-alkylguanine-DNA alkyltransferase (MGMT) is a universal DNA repair protein involved in the DNA direct reversal repair pathway that copes with alkylating carcinogens. Reduced MGMT expression as well as enzyme activity may result in an increased susceptibility to cancers. To elucidate the role of sequence variation in MGMT in the etiology of lung cancer, we conducted a comprehensive association study focusing on linkage disequilibrium (LD) structure of common variations across the MGMT sequence and its modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 37 publications
(46 reference statements)
1
57
0
Order By: Relevance
“…The controls had no history of cancer and were frequency matched to each set of cancer patients on age (F 5 y), sex, and residential area (urban or countryside). The most parts of these case-control sets have been also published previously (28,29). The distributions of selected characteristics by case-control status are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The controls had no history of cancer and were frequency matched to each set of cancer patients on age (F 5 y), sex, and residential area (urban or countryside). The most parts of these case-control sets have been also published previously (28,29). The distributions of selected characteristics by case-control status are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Quality control was performed as described previously in association with studies in lung cancer. 28 …”
Section: Genotype Assaymentioning
confidence: 99%
“…The study population and subject characteristics were described elsewhere (17). In brief, this hospital-based case-control study included 500 histopathologically confirmed incident lung cancer patients and 517 cancer-free controls, frequency-matched to the cases on age, sex, and residential areas.…”
Section: Methodsmentioning
confidence: 99%